EFFECT OF PARTIAL AND COMPLETE NEPHRECTOMY ON VARIOUS BLOOD PARAMETERS IN DOGS - S. M. W. Latif; M. A. Khan; A. K. Mahmood; H. B. Rashid (Journal of Animal and Plant Sciences, 2007)
The present study was conducted to analyze the effects of partial and complete nephrectomy on various blood parameters in dogs. A total of eight dogs were divided into two groups (A and B) comprising four animals each. In group A, complete nephrectomy was performed, while partial nephrectomy was carried out in group B. Post-operatively, the comparative effects of the two techniques were evaluated on the basis of clinical parameters, blood chemistry, hematological findings and radiographic examination. It was concluded that neither of the operations significantly affected the blood chemistry of the animals, hence, these techniques can be used to save the life of patient in proportion to the extent of defect.
Keywords: Dogs; Nephrectomy; Clinical; Haematological and Radiographic.